AB0804 Increased Carotid Intima-Media Thickness in Psoriatic Arthritis Patients Compared with Systemic Lupus Erythematosus Patients and Healthy Controls. (9th June 2015) - Dünya, A.; Yarkan, H.; Cetin, P.; Can, G.; Akkoc, N.; Onen, F.
Abstract : Background: Patients with psoriatic arthritis (PsA) and systemic lupus erythematosus (SLE) are at increased risk of atherosclerosis. An increased carotid intima-media thickness (IMT) is considered to be a marker of early atherosclerosis. Objectives: The aim of this study was to investigate carotid IMT in patients with PsA and compare it with those in patients with SLE and healthy controls. Methods: Non-diabetic patients with PsA and age and body mass index (BMI) matched, non-diabetic patients with SLE, and healthy controls were included in this study. Bilateral carotid IMTs were evaluated by using B-mode ultrasonography in PsA patients and compared with those in SLE patients and healthy controls. Results: There were 42 PsA patients (30 female, 12 male; mean age: 45.36±8.9 years) who fulfilled CASPAR criteria and 38 patients (37 female, 1 male; 41.2±13.0 years) who fulfilled the 1982 revised American College of Rheumatology (ACR) criteria for SLE. Thirthy healthy hospital workers (27 female, 3 male; mean age 41.2±6.8 years) were recruited as healthy controls. The frequency of hiperlipidemia was found to be significantly higher in patients with PsA than SLE patients and healthy controls (p<0.001) but hypertension was more common in SLE patients (p=0.002). While serum CRP levels were higher in PsA patients than control patients and healthy controls, SLE patients had higher ESR levels than the both control groups (p<0.001). The mean carotid IMT was found to be higher in PsA patients (0.76mm ±0.15) in comparison with the SLE patients (0.58±0.11) and healthy control group (0.57±0.12) (p<0.001). Conclusions: This study shows that carotid IMT measurements are higher in PsA patients than SLE patients and healthy controls. A higher hyperlipidemia frequency and male predominancy in PsA patients may be partly responsible for the increased carotid IMT compared with SLE patients. Disclosure of Interest: None declared